Pemberdayaan Masyarakat Melalui Mawah Ternak Kambing Gampong Blangreumah Kecamatan Meurah Mulia Kabupaten Aceh Utara - Ismaulina Ismaulina; Asma Savitri (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
Empowering the people of Gampong Blang Reumah, Meurah Mulia District, North Aceh Regency in training in goat farming technical skills with the mawah system and simple financial reports has become a solution to increasing people's income and creating jobs in the village. The results of this service provide positive benefits for the community regarding appropriate knowledge and skills in raising goats with the mawah system and also understand how to prepare simple financial reports to manage their business. Communities are more confident and independent and help them achieve a better life. This training also has a positive and sustainable impact in increasing people's income and creating jobs. With the cooperation and support from the local government, community and other related parties, it is ensured that the empowerment program will continue to be sustainable and will optimize the results achieved.